2010
DOI: 10.1371/journal.pone.0009077
|View full text |Cite|
|
Sign up to set email alerts
|

Responses to Environmental Enrichment Differ with Sex and Genotype in a Transgenic Mouse Model of Huntington's Disease

Abstract: BackgroundEnvironmental enrichment (EE) in laboratory animals improves neurological function and motor/cognitive performance, and is proposed as a strategy for treating neurodegenerative diseases. EE has been investigated in the R6/2 mouse model of Huntington's disease (HD), where increased social interaction, sensory stimulation, exploration, and physical activity improved survival. We have also shown previously that HD patients and R6/2 mice have disrupted circadian rhythms, treatment of which may improve co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 39 publications
5
54
1
Order By: Relevance
“…3). There were trends for earlier male mortality (as found in some prior reports: [41, 43]), regardless of diet treatment. There was a trend for the KD to reduce lifespan in females, but not males (Fig.…”
Section: Resultssupporting
confidence: 81%
“…3). There were trends for earlier male mortality (as found in some prior reports: [41, 43]), regardless of diet treatment. There was a trend for the KD to reduce lifespan in females, but not males (Fig.…”
Section: Resultssupporting
confidence: 81%
“…It is possible that the previous report of increased survival in R6/2 mice after TG2 ablation could be modulated by the CAG repeat of the model studied. Another possible explanation as to why we did not see difference in R6/2 survival after TG2 ablation may be because of the housing conditions utilized in our study, which have been shown previously to improve survival [34], [35]. Since our goal is to uncover robust targets for HD, we provided the animals with a moderate enriched environment (namely: group housing, a range of bedding, plastic bones and tunnels) as well as easy access to food and water.…”
Section: Discussionmentioning
confidence: 95%
“…All mice were kept on a 12-hour light cycle (lights on at 0700) and individually housed with ad libitum access to food and water. Although group housing is known to provide environmental enrichment and social benefits to mice (Balcombe, 2006), we opted for individual housing to facilitate comparisons of our results with studies from our lab as environmental enrichment is known alter the phenoptype of R6/2 mice (Wood et al, 2010). In fact, individual housing is appropriate for mice with a surgically implanted headstage (see below).…”
Section: Methodsmentioning
confidence: 99%